Positional Behavior Of Robinson’s Banded Langur (Presbytis femoralis robinsoni) - Badrul Munir, Md Zain; Muhammad Nurismadee, Abdul Manan; Muhammad Abu Bakar, Abdul Latiff; Norlinda, Mohd Daut; Mohd Ridhwan, Abd Rahman @ Tahir (UMT, 2019)
Presbytis femoralis robinsoni, locally known as the ‘lutong ceneka’, is an endemic femoralis subspecies to the northern part of Peninsular Malaysia and southern Thailand. This langur warrants immediate conservation attention, as it is categorized as Near Threatened by the International Union for Conservation of Nature (IUCN), with a declining numbers of population trend and being threatened with numerous conservation issues.With poor understanding on population status and unresolved conservation framework in Malaysia, data on behavioral ecology such as positional behavior of P. f. robinsoni are non-existent in Malaysia. Thus, this study describes the first record on qualitative aspects of the positional behavior of Robinson’s banded langur (P. f. robinsoni) in the Sungai Sedim Recreation Forest (SSRF), Kedah, Malaysia. The positional behaviors of P. f. robinsoni in SSRF involve sitting, lying, quadrupedal standing, bipedal standing, clinging, and forelimb suspension. These varieties of observed positional modes may be identified as it may related to the primary forest habitat conditions. Understanding langur behavioural responses to their natural habitat environments are useful in developing an effective conservation framework for the Robinson’s banded langur in Malaysia.